Peran Guru dan Orang tua dalam Proses Pembelajaran pada Masa Pandemi Covid-19 di SMA Negeri 3 Kabupaten Tolitoli - Faisal, Moh.; Hamid, Abdul (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
This research was conducted at SMA Negeri 3 Tolitoli, Baolan District, Baru Village, Tolitoli Regency. The purpose of this research is to know the role of teachers in the learning process during the Covid-19 pandemic, know the role of parents in the learning process during the Covid-19 pandemic, and know the interaction of the role of teachers and parents in improving the learning process during the Covid-19 pandemic. The subjects of this study were 2 Geography Subject Teachers, 2 Parents, and 2 Students. Collecting data using observation, interviews, and documentation. The results showed that the teacher's role in the learning process during the Covid-19 pandemic was to prepare material and learning evaluation results, have a responsibility to ensure the safety or health of students by providing active reinforcement and providing understanding to students to comply with all health protocols, prioritizing facilitation of learning. students, providing emotional support for students, parents, and also families, and communicating and collaborating with school principals, parents/families of students to support the learning process. In addition, there are also teachers who monitor students either via WA chat or meet directly with parents in the learning process for children during the Covid-19 pandemic, which has helped provide internet quota for children to use when learning online. There are parents who try to control the child and help the child in completing the tasks from the teacher, this is done so that the child can continue to study regularly and be more enthusiastic. Parents and teachers have interacted well to help the learning process for children during the Covid-19 pandemic, teachers or parents help each other in carrying out their roles to create conducive learning so that children can be even more active in learning during the Covid-19 pandemic.